Pacing accuracy during an incremental step test in adolescent swimmers - Scruton A; Baker J; Roberts J; Basevitch I; Merzbach V; Gordon D (Dove Medical Press, 2015)
Adrian Scruton, James Baker, Justin Roberts, Itay Basevitch, Viviane Merzbach, Dan Gordon Sport and Exercise Sciences Research Group, Anglia Ruskin University, Cambridge, UK Abstract: To assess pacing accuracy in a group of adolescent swimmers during an incremental step test. Fifteen well-trained swimmers (age 15±1.5 years; height 170.2±8.8 cm; mass 60.2±6.6 kg), completed two 7×200 m tests, separated by ~72 hours. They swam to a predetermined incrementally increasing pace per step and were instructed to swim at even pace. Upon completion of each step, rating of perceived exertion, heart rate and blood lactate were recorded. Significant differences observed for both trials between actual and predicted swim time (P<0.05). Significant differences also observed between the first and second 100 m of each step in trial 1 for step 1 (P=0.001, effect size [ES] =0.54), step 2 (P=0.0001, ES =0.57), step 4 (P=0.0001, ES =0.53), step 5 (P=0.005, ES =0.65), step 6 (P=0.0001, ES =0.50), and step 7 (P=0.0001, ES =0.70). Similar responses witnessed for trial 2 (P<0.05). Findings suggest that the finite anaerobic capacity was engaged sooner than would normally be anticipated, as a function of an inability to regulate pace. This is proposed to be a consequence of the volume of exposure to the biological and psychological sensations and cognitive developmental status. Given the apparent error in pacing judgment exhibited in this population group, caution should be applied when adopting such tests to monitor training responses with adolescent athletes, and alternate means of modulating pace be investigated. Keywords: effort regulation, children, exercise testing, perception